2020
DOI: 10.1186/s12943-020-01182-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Role of HDACs in normal and malignant hematopoiesis

Abstract: After the publication of this work [1], the authors note that there are no figure legends in published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Three of them contain the Zn 2+ dependent catalytic domain, which are referred to as classical HDACs, and class III members are NAD +dependent, called sirtuins, which possesses deacetylase activity but is unrelated to HDACs, and will not be involved here. Distinguished by structure, enzymatic function, and localization, they display similar and specific functions during the regulation of gene expression (13,21,58).…”
Section: Hdacs Classification and Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three of them contain the Zn 2+ dependent catalytic domain, which are referred to as classical HDACs, and class III members are NAD +dependent, called sirtuins, which possesses deacetylase activity but is unrelated to HDACs, and will not be involved here. Distinguished by structure, enzymatic function, and localization, they display similar and specific functions during the regulation of gene expression (13,21,58).…”
Section: Hdacs Classification and Functionsmentioning
confidence: 99%
“…Although HDAC mutations in AML are relatively rare compared to solid tumors, HDAC proteins are abnormally recruited to oncogenic fusion proteins, such as AML1-ETO, CBFB-MYTH11, PML-RARa, and MLL-fusions, which function as vital roles in onsetting and promoting the progress of leukemogenesis (4,13,31). And HDAC inhibitors, as a series of compounds that neutralize the activities of HDACs, have long been utilized in treatment of AML for pre-clinical studies, which have some extend shown beneficial outcomes (26,27,30,31).…”
Section: Hdacs In Leukemogenesismentioning
confidence: 99%
See 3 more Smart Citations